Growth plate abnormalities in pediatric cancer patients undergoing phase 1 anti‐angiogenic therapy: A report from the children's oncology group phase I consortium. Issue 1 (24th September 2014) - Voss, Stephan D.; Glade‐Bender, Julia; Spunt, Sheri L.; DuBois, Steven G.; Widemann, Brigitte C.; Park, Julie R.; Leary, Sarah E. S.; Nelson, Marvin D.; Adamson, Peter C.; Blaney, Susan M.; Weigel, Brenda
<x xml:space="preserve">Abstract</x> Background Pre‐clinical studies suggest that anti‐angiogenic agents may be toxic to the developing growth plate. The purpose of this study was to evaluate the incidence of growth plate abnormalities in children with refractory cancer undergoing anti‐angiogenic therapy. Procedure Targeted radiographic studies from 53 subjects enrolled on six separate Children's Oncology Group Phase 1 and Pilot Consortium clinical trials evaluating new anti‐cancer agents interfering with angiogenesis were reviewed. Subjects received tyrosine kinase inhibitors with anti‐angiogenic effects (n = 35), monoclonal antibodies targeting vascular endothelial growth factor (VEGF) (n = 13), or angiopoietin (n = 5). Radiographs of their distal femur/proximal tibia were obtained at baseline. Follow‐up radiographs were obtained after odd‐numbered treatment cycles in patients with open growth plates who did not experience disease progression prior to cycle 3. Results Baseline and follow‐up growth plate radiographs were acquired in 48/53 (90%) of patients. Five patients (9.4%), all of whom received a specific VEGF/VEGFR blocking agent (sunitinib [n = 1] or pazopanib [n = 4]), had growth plate abnormalities. Four patients had growth plate widening that was apparent on at least two successive radiographs, but was not confirmed by MRI. The fifth patient had progressive growth plate widening and evidence of physeal cartilage hypertrophy on MRI. Subsequent off treatment radiographs showed that the growth plate changes were reversible. Conclusion Growth plate abnormalities occur in a small, but relevant number of patients undergoing anti‐angiogenic therapy. These results support the need for growth plate monitoring in children with open growth plates who are receiving anti‐angiogenic therapy, and for improved methods to assess toxicity of anti‐angiogenic agents to the developing skeleton. Pediatr Blood Cancer 2015;62:45–51. © 2014 Wiley Periodicals, Inc.